2012
DOI: 10.1515/znc-2012-5-608
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Phenolic Compounds from the Egyptian Red Sea Seagrass Thalassodendron ciliatum

Abstract: Five fl avonoids (rutin, asebotin, 3-hydroxyasebotin, quercetin-3-O-β-D-xylopyranoside, and a racemic mixture of catechin) and caffeic acid were isolated and identifi ed for the fi rst time from seagrass, Thalassodendron ciliatum, collected from the Hurghada region in Egypt. The crude extract and the isolated pure compounds were evaluated for their cytotoxic activities against HCT-116, HEPG, MCF-7, and HeLa human cancer cell lines, for their antiviral activity against Herpes Simplex and hepatitis A viruses, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Gavagnin et al [17] reported that syphonoside from H. stipulacea inhibited apoptosis in some of the cell lines investigated. Moreover, crude extracts of the seagrass Thalassodendron ciliatum exhibited cytotoxic activity against HCT116 cells with an IC 50 of 4.2 µg/mL [18]. However, as extracts of the seagrass Halophila stipulacea had a similar activity on a non-carcinogenic cell line and did not show activity on spheroids from the 3D cell culture, they are not regarded as interesting material for future works on anticancer activities.…”
Section: Discussionmentioning
confidence: 99%
“…Gavagnin et al [17] reported that syphonoside from H. stipulacea inhibited apoptosis in some of the cell lines investigated. Moreover, crude extracts of the seagrass Thalassodendron ciliatum exhibited cytotoxic activity against HCT116 cells with an IC 50 of 4.2 µg/mL [18]. However, as extracts of the seagrass Halophila stipulacea had a similar activity on a non-carcinogenic cell line and did not show activity on spheroids from the 3D cell culture, they are not regarded as interesting material for future works on anticancer activities.…”
Section: Discussionmentioning
confidence: 99%
“…Thalassodendrone reduced cytopathogenicy with an IC 50 of 1.96 µg/mL [124]. The phenolic compounds asebotin (2 ,4,6 -trihydroxy-4methoxydihydrochalcone 2 -O-β-d-glucopyranoside), quercetin-3-O-β-d-xylopyranoside and trans-caffeic acid ( Figure 3C) isolated from the same seagrass showed viral activity percentage reduction (96%, 70%, and 53% respectively) by plaque formation assay against HSV-1 at 2 mM [125]. Hawas et al [126] isolated Thalassiolin D (diosmetin 7-O-β-glucoside-2"-sulphate) ( Figure 3C), a flavone O-glucoside sulphate, from the seagrass Thalassia hemprichii.…”
Section: Seagrassesmentioning
confidence: 89%
“…Three isolated khayanolides, named Thaixylomolins I, K, and M, exhibited anti-H1N1 activities, with IC 50 values of 77.1, 113.5, and 121.5 µM, respectively [128]. Even if a huge number of secondary metabolites have been extracted from mangroves [119,122,125], only a small number of studies reported antiviral compounds ( Table 5).…”
Section: Mangrovesmentioning
confidence: 99%
“…Along with rosmarinic acid, caffeic acid and chlorogenic acid found to be present in some trace amounts, since caffeic acid acts as a precursor for roamarinic acid in the shikimic acid biosynthesis. It was also been reported that the predominance of caffeic acid was accumulated in the leaves of P. oceanica [104] and Thalassodendron ciliatum [105]. Jeyapragash et al [51] from Halodule pinifolia, which includes caffeic acid, coumaric acid, chlorogenic acid and rosmarinic acid which found predominant than other compounds.…”
Section: Seagrasses-a Source For Marine Based Drug Discoverymentioning
confidence: 94%